ANALISIS PERLINDUNGAN TATA RUANG TOKO SEBAGAI SUBJEK MEREK TIGA DIMENSI DI INDONESIA - Rebecca, Aicha Grade; Marlyna, Henny (Jurnal Yuridis, 2025)
In line with the development and the trend of Creative Economy business in Indonesia, the creation of business that are “Design Centric” by nature or having an orientation towards aesthetic design are flourishing, specifically lifestyle business who invested their time and money to build store layout that could be a brand signifier on the business that they have. Although, until now there are still a legal polemic in relations of which Intellectual Property (“IP”) Object that are suitable to protect store layout that include Three Dimensional Marks, Industrial Design and Copyright in protecting store layout. This Journal would analyze the concept of store layout, and the existing legal framework that have been enacted to protect store layout overseas, especially those relating to three dimensional marks. After that, this Journal would analyze the legal inconsistencies between the law of Trademarks, Industrial Design and Copyright in protecting store layout. The usage of qualitative descriptive analysis will be used to have perspective in relations about this phenomena, especially those from chosen regulators. At the end of the Journal, the writer’s hope that there will be an understanding of the problem of store layout protection based otn the existing system in Indonesia. Furthermore, the writers also hope that it will lead to the best available solution to fix the effectivity of legal protection of store layout as three dimensional marks subject.